2016
DOI: 10.1007/s00427-016-0556-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative expression study of sipa family members during early Xenopus laevis development

Abstract: The signal-induced proliferation-associated (SIPA) protein family belongs to the RapGAP protein superfamily. Previous studies mainly focused on the expression and function of SIPA genes in vertebrate neuronal tissue. Only limited data about the embryonic expression pattern of the genes are currently available. Our study provides the first expression analysis of sipa1, sipa1l1, sipa1l2, and sipa1l3 during early development of the vertebrate organism Xenopus laevis. In silico, analysis revealed that all genes ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…In a previous study, we confirmed the genomic conservation of the sipa1l3 gene across species (Dolnik et al, 2016). Here, we showed a similar expression and function of Sipa1l3 in Xenopus compared with mouse and zebrafish (Greenlees et al, 2015;Lachke et al, 2012;Rothe et al, 2016). Consistent with the mouse model and human patients (Evers et al, 2015;Greenlees et al, 2015), eye and lens sizes were significantly reduced in Sipa1l3-deficient Xenopus embryos.…”
Section: Sipa1l3 Is Required For Ocular Developmentsupporting
confidence: 87%
See 3 more Smart Citations
“…In a previous study, we confirmed the genomic conservation of the sipa1l3 gene across species (Dolnik et al, 2016). Here, we showed a similar expression and function of Sipa1l3 in Xenopus compared with mouse and zebrafish (Greenlees et al, 2015;Lachke et al, 2012;Rothe et al, 2016). Consistent with the mouse model and human patients (Evers et al, 2015;Greenlees et al, 2015), eye and lens sizes were significantly reduced in Sipa1l3-deficient Xenopus embryos.…”
Section: Sipa1l3 Is Required For Ocular Developmentsupporting
confidence: 87%
“…First, we determined the spatiotemporal expression pattern of sipa1l3 using an antisense RNA probe. As we have shown previously (Rothe et al, 2016) and as observed in mouse and zebrafish (Greenlees et al, 2015;Lachke et al, 2012), sipa1l3 transcripts were clearly detectable in the developing Xenopus eye including the early anterior neural plate where the eye field is localized (Fig. 1A, upper row, white arrowheads).…”
Section: Sipa1l3 Depletion Causes Ocular Defects In Xenopus Laevissupporting
confidence: 84%
See 2 more Smart Citations
“…All SIPA family members share common domains, namely an N-terminal Rap GAP domain (Rap-GTPase activating domain), a PDZ domain and a C-terminal coiled-coil domain carrying a leucin-zipper motif. SIPA1L1-SIPA1L3 contains an additional domain of unknown function (DUF3401) [6][7][8]. Base on its functional structure, we hypothesized that SIPA1L3 play an important functional role in lung cancer development.…”
Section: Introductionmentioning
confidence: 99%